Use of the National Cancer Institute Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events to assess treatment tolerability in pulmonary arterial hypertension: qualitative patient research findings in current and former users of oral selexipag - Stacy Davis; Teresa Edwards; Lindsey Norcross; Sheri Fehnel; Amélie Beaudet; Marie Eckart; John Fastenau (SpringerOpen, 2023)
Abstract Background Understanding patients' perspectives regarding drug tolerability, in addition to effectiveness, provides a complete picture of the patient experience and supports more informed therapeutic decision-making. The item library of the National Cancer Institute's Patient-Reported Outcomes version of the Common Terminology Criteria for Adverse Events (PRO-CTCAE) was developed to measure patient-reported frequency, severity, and interference of adverse events (AEs) associated with cancer therapies. This qualitative interview study assessed the suitability of items selected from the PRO-CTCAE library for assessing tolerability of selexipag, a medication targeting the prostacyclin pathway for patients with pulmonary arterial hypertension (PAH). Methods Two rounds of 10 qualitative, web-assisted telephone interviews following a semi-structured guide were conducted in individuals with recent experience taking oral selexipag for PAH. Each interview included concept elicitation to gather participants' perspectives on symptomatic AEs (type, frequency, severity, and interference) and cognitive debriefing of PRO-CTCAE items addressing the most frequently reported AEs of oral selexipag. Results Interviews were conducted with 20 participants with PAH (mean [range] age 50 [24-68] years; 75% female; 85% in World Health Organization Functional Class II-III), comprising different races/ethnicities, levels of education, and employment status. Fifteen participants were currently treated with selexipag; five had taken selexipag for ≥ 6 months before discontinuing. The most frequently reported AEs included headache, jaw pain, and nausea (n = 15, 12, and 10 participants, respectively). Diarrhea and headache were identified as the most bothersome AEs by 5 and 4 participants, respectively. Some AEs were transitory (e.g., jaw pain); others were long-lasting (e.g., muscle pain). Based on findings from Round 1 interviews, a flushing item was added and the PRO-CTCAE general pain item was modified to be specific to jaw pain for testing in Round 2. Interview findings identified the following AEs as relevant to assess in a PAH clinical trial: nausea, vomiting, diarrhea, flushing, jaw pain, headache, aching muscles, and aching joints. Conclusions The PRO-CTCAE items selected in this study and the additional symptomatic AEs identified as patient-relevant have the potential to be included in assessments capturing the patient perspective on tolerability in future studies of selexipag and possibly other PAH therapies.